Child and Home Predictors of Children's Name Writing. (11th December 2012) - Gerde, Hope K.; Skibbe, Lori E.; Bowles, Ryan P.; Martoccio, Tiffany L.
Abstract : The current study used dominance analysis to investigate the relative importance of multiple factors on children's (ages 3–5; mean age of 47.3 months) name writing skill when they enter preschool. Children (n = 103 ) were tested individually at the beginning of preschool on six factors thought to be important for name writing success: letter knowledge, decoding, motor skills, problem behaviors, self-regulation, and home literacy environment. Collectively, these variables explained 37.1% of the variation in children's name writing, but the importance of each factor differed widely. Children's knowledge of capital letters (11.8%) and their motor development (11.8%) were the most important for children's name writing whereas the home learning environment (2.3%) and reported problem behaviors (1.5%) were the least important factors. These findings suggest that researchers and teachers should focus on letter knowledge and motor development in understanding and promoting children's name writing skills.